Quality by design for enabling RNA platform production processes - Daniel,S; Kis,Z; Kontoravdi,K; Shah,N (Trends in Biotechnology, 2022)
RNA-based products have emerged as one of the most promising and strategic technologies for global vaccination, infectious disease control and future therapy development. The assessment of critical quality attributes, product-process interactions, relevant process analytical technologies, and process modeling capabilities can feed into a robust Quality by Design (QbD) framework for future development, design and control of manufacturing processes. Its implementation will help the RNA technology to reach its full potential and will be central in the development, pre-qualification and regulatory approval of rapid response, disease-agnostic RNA platform production processes.